3D integrated hollow lightweight E-glass fiber reinforced epoxy composites with excellent electromagnetic wave absorption and thermal insulation. (12th April 2023) - Cao, Yaru; Qing, Yuchang; Li, Yang; Nan, Hanyi; Yan, Ziyi; Yao, Haoyang; Wen, Jiahao; Wang, Chunhai; Luo, Fa
Abstract: Electromagnetic parameters regulation is still a formidable task in developing lightweight, wide bandwidth, and high-efficiency electromagnetic wave (EMW) absorption materials. Here, a facile technique has been proposed by taking full advantage of 3D integrated hollow E-glass fabric, which is characterized by the typical spatial characteristic forms (U-shaped hollow structures at the level of the centimeter) to regulate EM parameters, optimizes impedance matching and enhances the absorption ability of graphene nanosheets (GNs). The minimum reflection loss (RL) of the 3D integrated hollow GN/resin composites reached −49.3 dB with an effective absorption bandwidth (RL < −10 dB) of 12.4 GHz. Comparing the density of the novel composites to that of conventional EMW absorption materials, it is lowered by an order of magnitude (0.31 g cm −3 ). Moreover, a good temperature drop of 100 °C was observed under an infrared thermal imager. The results indicate that the composites not only effectively alter the propagation path of EMW, increase the EM energy losses in the transmission process, but also block thermal convection and show excellent thermal insulation properties. This study provides an aggressive strategy and effective method for the development of lightweight ultra-broadband absorbing and excellent thermal insulation composites. Graphical abstract: Image 1 Highlights: 3D integrated hollow structure epoxy matrix lightweight composites have been prepared. Composites combine excellent microwave losses and thermal insulation performance. The effective bandwidth is up to 12.4 GHz with a low density of 0.31 g cm −3 .